2020
DOI: 10.1016/j.heliyon.2020.e04127
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and job quality in Mexico: 2005–2019

Abstract: This investigation analyzes labor implications of employment procurement through friends and family on wages, workers' benefits and job longevity in comparison to other job search methods in Mexico during 2005-2019. Various econometric models are performed. For salary, fixed effects by city and year will be estimated through Pooled Ordinary Least Squares (OLS). Second, it is analyzed if jobs obtained through friends and family are more likely to provide benefits equal to or greater than those required by law, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…We would like to note that in the current research the correlation among variables might have been tested previously, yet little attention has been paid to investigating the mechanism linking personality traits and networking behavior. Prior studies indicated that networking behavior for employment is positively related to the number of job interviews and offers, employment status (e.g., salary), person-job fit, and person-organization fit (Forret, 2014; Le, 2022; Lin & Le, 2019; Rodríguez-Villalobos & Rangel-González, 2020). However, the absence of studies about mediating mechanisms between personalities and networking behavior may be the reason preventing managers from understanding how to promote job seekers with different personalities to apply for job search networking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to note that in the current research the correlation among variables might have been tested previously, yet little attention has been paid to investigating the mechanism linking personality traits and networking behavior. Prior studies indicated that networking behavior for employment is positively related to the number of job interviews and offers, employment status (e.g., salary), person-job fit, and person-organization fit (Forret, 2014; Le, 2022; Lin & Le, 2019; Rodríguez-Villalobos & Rangel-González, 2020). However, the absence of studies about mediating mechanisms between personalities and networking behavior may be the reason preventing managers from understanding how to promote job seekers with different personalities to apply for job search networking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…La literatura internacional acerca de capital social y mercado laboral, pone especial atención a la asociación entre amigos y familiares como referentes de ofertas de trabajo. Por lo tanto, en México es pertinente profundizar en los mecanismos de búsqueda de trabajo y en el papel que desempeña el capital social (Charles-Leija et al, 2018;Méndez et al, 2018;Rodríguez-Villalobos & Rangel-González, 2020).…”
Section: Introductionunclassified